Firm location (Geography) and value effects - Huang, Shuzhuang (2010)
Past literature has seen a rising importance of geographical proximity in supplier-customer relationships. The purpose of this paper is to examine whether being located closer together adds value to supplier-customer relationships from the perspective of supplier firms. Our data consists of all North American supplier and customer firms that have partnerships in the period 1994 to 1997. We want to find out if: (1) Suppliers across industries produce more for geographically-proximate customers, and (2) Suppliers that are located close to customers yield higher value. Geographical proximity is measured using same state, driving distance and time while proportion of supplier sales attributable to a customer and return on assets are used to measure supplier dependency on customers and profitability of supplier firms respectively. In this study, we test our hypotheses using linear regression. Our results show that Hypothesis 1 is supported by low R&D intensive suppliers located in the same state as customers in the durable goods manufacturing industry. Similar results apply to all supplier firms in the non-manufacturing industry regardless of the amount of R&D expenditure. Hypothesis 2 stands only for durable goods manufacturing suppliers located in different states as customers. This study enhances understanding of the significance of geographical proximity in supplier-customer relationships by discussing the financial aspect of business. Most importantly, managers in supplier firms of various sectors can make better location decisions that will help increase sales and improve firm profitability in the future.